2019
DOI: 10.1111/ijlh.13043
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a reference range for thromboelastograph parameters in the neonatal period

Abstract: IntroductionAcquired coagulation disorders are a common cause of neonatal bleeding. The thromboelastograph (TEG) comprehensively assesses haemostatic processes in the body. Unfortunately, the reference range of TEG parameters in the neonatal period has not yet been evaluated, which limits the use of the TEG in neonates. In this study, we aimed to establish the reference range of TEG parameters for the neonatal period.MethodsThis study included 371 full‐term infants (≥37 weeks of gestation), and we divided thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(76 reference statements)
1
16
0
1
Order By: Relevance
“…And in clinical practice, we should take neonatal sampling sites into consideration when choosing RIs for platelet parameters. A recent study showed that neonatal age had a significant effect on the parameters regarding coagulation [28]. And we found a slight variation in PLT in the first days of life.…”
Section: Discussionsupporting
confidence: 57%
“…And in clinical practice, we should take neonatal sampling sites into consideration when choosing RIs for platelet parameters. A recent study showed that neonatal age had a significant effect on the parameters regarding coagulation [28]. And we found a slight variation in PLT in the first days of life.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study showed that neonatal age had a signi cant effect on the parameters regarding coagulation. [32] And we found a slight uctuation in PLT in the rst days of life. Of note, a multicentre study recruiting a large neonate cohort [4] reported that PLT values changes with two peak sinusoids at 2-3 weeks and 6-7 weeks of postnatal age.…”
Section: Discussionmentioning
confidence: 61%
“…In fact, the rationalization and reduction of (unnecessary) blood product transfusion is one of the most important advantages of VET-based pediatric bleeding management strategies. [8][9][10] Reference values for pediatric patients have been evaluated for ROTEM, [11][12][13] TEG, [14][15][16][17][18][19][20] and the Sonoclot system. 21 The main difference for VET reference ranges between children and adults are displayed in Table 1.…”
Section: Description Of Vetmentioning
confidence: 99%
“…22 However, it needs to be mentioned that the definition of age groups was not uniformly applied within the cited papers. While in the study of Liu et al 19 data from three neonatal age groups (1 day, 2-7 days, 8-28 days) were analyzed separately, Oswald and colleagues 11 have pooled data of children from 1 day to 3 months of age, together labeled as the youngest age group. As such, comparison of data and subsequent interpretation should be done carefully.…”
Section: Description Of Vetmentioning
confidence: 99%